Extracorporeal hyperoxygenation therapy (EHT) for CO poisoning: in vitro and in vivo feasibility of a full-scale batch system - Niklas B. Steuer; Hannah Lüken; Peter C. Schlanstein; Matthias F. Menne; Christiane Hoffmann; Cavan Lübke; Thomas Schmitz-Rode; Sebastian Victor Jansen; Ulrich Steinseifer; Rüdger Kopp (Scientific Reports)
Abstract Carbon monoxide (CO) poisoning is one of the most common causes of injury and death from poisoning. The primary objective of therapy is to eliminate CO from the patient as quickly as possible to prevent acute and long-term effects. The ideal treatment is hyperbaric oxygen in a pressure chamber. However, pressure chambers are scarce, and therefore, the most common treatment is normobaric oxygen (NBO), which, however, has limited efficacy. Here, we present a full-scale batch system for extracorporeal hyperoxygenation therapy (EHT), which facilitates CO elimination extracorporeally by increasing the dissolved oxygen concentration in the blood. The EHT was characterized in vitro, resulting in a minimum carboxyhemoglobin half-life of 3.26 ± 0.11 min. In large animal trials the EHT reduced the median carboxyhemoglobin half-life by 42% (29.77 min EHT vs. 70.8 min control (NBO)). However, the EHT also induced oscillations in hemodynamic pressures due to changes in the animals’ circulatory volume during operation. After optimization, the EHT could be a promising option for treating CO poisoning.